The potential of microsatellite markers on the identification of various ethnic alleles in Indonesia - Harja, Husnul Sri Mulyani; Muthiadin, Cut (Genetikawan Muda Indonesia, 2023)
Indonesia is an archipelagic country with a high level of population diversity such as religion, ethnicity, culture and also genetic diversity. Environmental factors also have an impact on the genetic variation and diversity of the population, including high mobility and migration triggering the tendency for inter-ethnic marriages to occur. This environmental factor is one of the reasons for research based on DNA analysis on ethnicity in Indonesia for the purpose of forensic identification. One of the DNA analyzes for forensic identification is the microsatellite DNA analysis method with a high sensitivity level.